Supporting spirituality in the care of older people living with dementia: a hermeneutic phenomenological inquiry into nurses' experiences - Toivonen, Kristiina; Charalambous, Andreas; Suhonen, Riitta (My University, 2018)
BackgroundSpirituality is defined as a search for answers to existential questions about the meaning of life and the individual's relationship with the sacred or transcendent. This relationship may or may not involve affiliation with a specific religion. Studies on spirituality have focused on palliative care, and there are limited studies into the spirituality in the care of older people with dementia. AimTo describe the experiences of nurses supporting spirituality in the care of older people living with dementia. MethodThis study, informed by Heideggerian hermeneutic phenomenology, was conducted in 2014/15. Data were collected by interviewing a purposive sample of 17 nurses. ResultsSupporting the spirituality of older people with dementia was seen as understanding their spirituality within a framework of person-centeredness and individuality. The participants came to understand the spiritual needs of older people with dementia through both verbal and nonverbal expression and by learning about older people's individual spiritual backgrounds. Meeting spiritual needs meant approaching the person with dementia as a valuable human as well as paying attention, to and supporting, his/her personal philosophy of life within nursing care. ConclusionLearning and developing an understanding of the spiritual needs of older people with dementia is challenging. The nurses offered person-centred, spiritual care, to people with dementia from a variety of perspectives, which is important in the provision of comprehensive care. There is a need to find usable tools to help nurses to learn and understand the individual spiritual needs of older people with dementia and to explore how these older adults experience having their spirituality supported within their nursing care.
Keywords: Qualitative approaches; Phenomenology; Hermeneutics; Gerontology; Dementia; Elder care; Spirituality